PERBAIKAN DAN PENGENDALIAN KUALITAS PADA PROSES PERCETAKAN LABEL KEMASAN DARI PLASTIK DENGAN MENGGUNAKAN METODE SIX SIGMA DI CV. SETIA ABADI, SURABAYA, JAWA TIMUR PERBAIKAN STRATEGI PEMASARAN BERBASIS KONSUMEN DI UD. INDAH MAKMUR, SURABAYA - Almon Andre Moniaga; Rosita Meitha Surjani; Gunawan Gunawan (Perpustakaan Universitas Surabaya, 2013)
UD. Indah Makmur a cosmetic product distributor located in Surabaya area. In a further development, it is almost certain that a large enough scale businesses like UD. Indah Makmur requires an information system to support the processes contained therein. But these allegations have to go through a reasonable and systematic reasons, and not just through the allegations or perceptions. Do distributing questionnaires as a means to obtain primary data include consumer behavior data to determine consumer behavior UD. Indah Makmur in making a purchase. The results of the questionnaire will be used as the input of the various statistical tests such as crosstab and MANOVA. In crosstab analysis, it was concluded that there is a relationship between the old and new customers with average variable interval message to UD. Indah Makmur and it was concluded that there is a relationship between consumer groups based on their location with average variable interval message to UD. Indah Makmur, with new consumer trends and consumers in the south more often than other groups to book. While the MANOVA analysis showed no differences between groups of consumers. In addition to the statistical analysis, as well as quadrant analysis and SWOT analysis as the basis of making a marketing strategy. Perform database creation because it is a requirement necessitated by UD. Indah Makmur. This is supported by the results of the questionnaire, the variables that go into the UD complaint. Indah Makmur, stockout is often the case, the difficulty of checking the amount of goods due to the variety of products that can be addressed by tll much use of information systems such as databases.